Introduction - Hvid, Helge (Nordic Journal of Working Life Studies, 2016)
Also in this issue, we present articles that represent working life research widely. Working life and the Nordic labor market model is examined in three articles: Two articles present studies about current challenges for the Nordic model illustrated by case studies of low-paid service work, largely done by migrant workers. A third article contributes to the understanding of the Nordic model through a study of employers’ involvement in active labor market policy. Two studies are dealing with employee involvement in the renewal and transformation of the public sector, respectively, on family-related social service and in hospitals. We present a study of how conflicts at the workplace affect the working environment with a large nongovernmental organization (NGO) as case. Finally, a study of how working conditions affects intention to retire is presented, with a university as case (...)